HOAKS, PENYAKIT KRONIS DALAM PERADABAN DIGITAL - Taufik, Cevi Mochamad; Bintang, Gilang (KOMUNIKA BANGSA, 2025)
. The new civilization of the social media era has arrived. Pulled from its inception, the presence of social media has been relatively long and has become a means for the public to obtain information. Until now, social media has almost replaced the role of mainstream media in delivering and providing public information services. However, even though it has been running for a relatively long time, it still raises problems regarding the clash of public logic in digesting information spread by social media content. The public often experiences confusion. Research shows that hoax content is created by parties who do not have the competence and expertise in reconstructing events. However, it is possible that there is also content that is deliberately created with the aim of being a hoax with the intention of destroying public belief and trust. Examined further, this is a side effect of the freedom and ease of operating social media. Therefore, to understand this problem, this study was conducted using a qualitative approach through the media content analysis method. The goal is to understand content that leads to error through content that is spread and distributed by social media account owners. The results of the study show that there are two entities that contribute to the stain on digital civilization through hoaxes spread by parties who do not have the capacity and groups of experts who are very capable of forming public opinion.